Transcriptome analysis reveals intermittent fasting-induced genetic changes in ischemic stroke. (13th February 2018) - Kim, Joonki; Kang, Sung-Wook; Mallilankaraman, Karthik; Baik, Sang-Ha; Lim, James C; Balaganapathy, Priyanka; She, David T; Lok, Ker-Zhing; Fann, David Y; Thambiayah, Uma; Tang, Sung-Chun; Stranahan, Alexis M; et al.
Abstract: Genetic changes due to dietary intervention in the form of either calorie restriction (CR) or intermittent fasting (IF) are not reported in detail until now. However, it is well established that both CR and IF extend the lifespan and protect against neurodegenerative diseases and stroke. The current research aims were first to describe the transcriptomic changes in brains of IF mice and, second, to determine whether IF induces extensive transcriptomic changes following ischemic stroke to protect the brain from injury. Mice were randomly assigned to ad libitum feeding (AL), 12 (IF12) or 16 (IF16) h daily fasting. Each diet group was then subjected to sham surgery or middle cerebral artery occlusion and consecutive reperfusion. Mid-coronal sections of ipsilateral cerebral tissue were harvested at the end of the 1 h ischemic period or at 3, 12, 24 or 72 h of reperfusion, and genome-wide mRNA expression was quantified by RNA sequencing. The cerebral transcriptome of mice in AL group exhibited robust, sustained up-regulation of detrimental genetic pathways under ischemic stroke, but activation of these pathways was suppressed in IF16 group. Interestingly, the cerebral transcriptome of AL mice was largely unchanged during the 1 h of ischemia, whereas mice in IF16 group exhibited extensive up-regulation of genetic pathways involved in neuroplasticity and down-regulation of protein synthesis. Our data provide a genetic molecular framework for understanding how IF protects brain cells against damage caused by ischemic stroke, and reveal cellular signaling and bioenergetic pathways to target in the development of clinical interventions.